Gonadal tumor development in 46, XX disorders of gonadal development. Issue 3 (29th July 2022) - Costanzo, Mariana; Touzon, María Sol; Marino, Roxana; Guercio, Gabriela; Ramirez, Pablo; Mattone, María Celeste; Pérez Garrido, Natalia; Bailez, María Marcela; Vaiani, Elisa; Ciaccio, Marta; Galluzzo Mutti, María Laura; Belgorosky, Alicia; et al.
Abstract: Background: Differences/disorders of sex development (DSD) are congenital conditions in which the development of chromosomal, gonadal, or anatomical sex is atypical. Objective: The aim of this study is to report the histological characteristics and immunoexpression patterns of gonadal parenchyma in patients with 46, XX testicular and ovotesticular DSD, with a focus on the detection of germ cell malignancies. Design: Inclusion criteria were SRY -negative 46, XX testicular and ovotesticular DSD with available samples from gonadal biopsy or gonadectomy for the review of histological findings. Gonadal histology was assessed on hematoxylin and eosin-stained sections and immunohistochemical analysis. Histopathological criteria from the last World Health Organization classification of urogenital tumors were used to identify undifferentiated gonadal tissue, gonadoblastoma, and dysgerminoma. Results: Median age at first histological evaluation of gonadal samples was 1.46 years (range: 0.16–16 years). Totally 15 patients were classified as ovotesticular and only 1 as testicular DSD. Most individuals had bilateral ovotestes (12/15). No histological alterations were found in the ovarian parenchyma, while signs of dysgenesis were seen in all cases of testicular parenchyma. In 4/15 ovotesticular DSD, a prepubertal biopsy failed to identify ovarian parenchyma. We detected early prepubertal preinvasive and invasive malignancies in this cohort (five patients had undifferentiated gonadal tissue, five gonadoblastoma, and one dysgerminoma). Conclusion: 46, XX disorders of gonadal development are historically considered at a low risk for germ cell cancer, and the need for assessment of gonadal histology has been questioned. The finding of early germ cell malignancies in our cohort brings awareness and needs further research.